Analisis Asi Ekslusif Pada Bayi 0-6 Bulan di Puskesmas Sirah Pulau Padang Kabupaten Ogan Komering Ilir Tahun 2023 - Septi Dasiani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Breast milk contains all the nutrients to build and provide energy, besides that breast milk also has various anti-infective substances. Respiratory tract infections are the main cause of infant mortality in Indonesia. This study aims to analyze the relationship between education, knowledge, work, attitude, support from health workers and the availability of breast milk. This type of research is quantitative research with a cross-sectional research design/approach, namely a type of research that emphasizes the time of measurement/observation of independent and dependent variables at the same time. The population and research sample were mothers who brought babies aged 0-6 months to the Puskesmas and Posyandu or were reached by researchers through door-to-door visits in Sirah Pulau Padang District, Ogan Komering Ilir Regency in 2023 totaling 523 people. Bivariate research results show that there is a relationship between education and exclusive breastfeeding for babies 0-6 months at the Sirah Pulau Padang Health Center, OKI Regency in 2023, there is a relationship between knowledge, there is a relationship between work, there is a relationship between attitudes, there is a relationship between staff support health, there is a relationship between the availability of breast milk and exclusive breastfeeding in infants 0-6 months at the OKI Padang Island Sirah Health Center and the most dominant factor with exclusive breastfeeding in infants 0-6 months at the Sirah Padang Island Health Center OKI, namely Knowledge Variable.